Self, Other and Other-Self: Going Beyond the Self/Other Binary in Contemporary Consciousness - Sami Schalk (Journal of Comparative Research in Anthropology and Sociology, 2011)
Primarily relying on the work of W.E.B. Du Bois and Niklas Luhmann, this article discusses the effects of the mass media on contemporary consciousness, identity and self/other relations. This article proposes an approach to the self/other binary which opens up the possibilities for relations between individuals by including a third term, the other-self, which allows for a fluid, contextualized understanding of the self in a spectrum of relatedness to others in any given moment.